A Narrative Inquiry of Live Video Streaming: Voices of EFL Teachers to Reflect on Their Online Learning - Fachri Ali; Khusnul Alimah (Universitas Muhammadiyah Yogyakarta, 2023)
Despite being widely investigated by previous studies in online learning, live video streaming (LVS) as a strategy for teaching English as a foreign language receives scanty attention. The present narrative inquiry aims to showcase an empirical insight into how live video streaming on Facebook is organized in online learning to fill this void. Two EFL teachers of a senior secondary school in Central Java, Indonesia, volunteered to participate in this study. Data were garnered through interviews and classroom observation. The data were analyzed using thematic analysis. The study’s findings demonstrated that teaching through LVS on Facebook assisted EFL teachers in managing their online learning. The LVS-mediated learning process portrayed teaching, social, and cognitive presence during online learning. This result indicates that the learning platform provides promising prospects for teachers to optimize online English-speaking courses. The study also explored several challenges the EFL teachers encounter when managing LVS in their online classes with material and media preparation, time allocation, and internet connection. This study concludes with some pedagogical implications for how a teacher as a curriculum designer engages students in learning English and empowers them in online learning.